Genetic and biological insights into Hydatigera taeniaeformis in invasive black rats from southern Chile - Alvarez Rojas, Cristian A.; Bonacic, Cristian; Salgado, Rodrigo; Peters, Lucia; Fredes, Diego; Rubio, André V.; Muñoz-Leal, Sebastián; Oyarzún-Ruiz, Pablo; Aguirre, A. Alonso (Frontiers in Veterinary Science, 2024)
IntroductionThis study investigates the genetic variability of Hydatigera taeniaeformis in black rats (Rattus rattus), a common tapeworm that infects cats and rodents worldwide. Despite its widespread presence and zoonotic potential, little is known about the genetic diversity of this parasite in the Americas.MethodsWe conducted DNA barcoding analysis using mitochondrial cox1 gene sequences using samples collected from 171 invasive wild black rats, captured in the temperate rainforest of Southern Chile. We also included two adult parasites isolated from road killed Kodkods (Leopardus guigna), a small felid species native to the Americas.ResultsOur findings revealed only two haplotypes, suggesting low genetic variability in a parasite that arrived in the Americas with the Spanish colonization.DiscussionThese haplotypes are more closely related to parasite populations from Peru, Africa, Australia, and Europe, suggesting an origin linked to the Spanish colonization, possibly from North Africa via the Canary Islands. The study also analyzed infection rates, parasite size, and their correlation with host body size, age, and weight, revealing significant patterns. These results provide new insights into the biogeography and genetic diversity of H. taeniaeformis in a new geographical area, enhancing our understanding of its evolutionary history.